An Analysis of the Allometric and Multifractal Features of a Development in the Urban-Rural Area in the Lower Reaches of the Yangtze River: 2012 Cross-Sectional Data of Four Provinces and One City. (13th May 2020) - Song, Zhi-jun; Chen, Yi; Li, Yun; Zhao, Xin
Abstract : The provinces of Jiangsu, Anhui, Jiangxi, and Zhejiang and the city of Shanghai in the lower reaches of the Yangtze River forming a concentrated distribution area of developed cities and rich villages in China are so called "the four provinces and one city, " which have experienced rapid and typical urban-rural development. By drawing on the perspective of allometric growth, this paper conducts fundamental analysis and multifractal analysis of 52 prefecture-level cities in four provinces and one city in the lower reaches of the Yangtze River. Fundamental analysis shows that there are different patterns of allometric growth in various areas of the region, as well as the emergence of diffusion in fundamental activities and of polarisation in advanced activities. Multifractal analysis also shows that the comprehensive regional development is dominated by large- and medium-sized cities, but various fields have different fractal spectrums and form six interrelated urban-rural integration modes. The multiple spatial dissymmetry disclosed in the analysis also shows that each field had its own allometric growth features during the regional development. This paper adopts the fitting function and the relevant parameters of the fractal dimension to quantify the evolution in particular fields. Analysis shows that the developments in prefecture-level cities are different and represent the regional evolution status; the urban-rural development in metropolises and small- and medium-sized cities is nonmainstream.